Navigating Ethical Dilemmas Of Generative AI In Medical Writing - Qurrat Ulain Hamdan; Waleed Umar; Mahnoor Hasan (Journal of Rawalpindi Medical College)
The history of humankind is marked by revolutionary inventions that completely transformed the quality and trajectory of human lives. Revolution and innovation are dynamic processes that have and will continue, at an increasing pace due to discoveries and inventions. Like the steam engine in the 18th century, electricity in the 19th century, and the Internet at the cusp of the 20th and 21st centuries, the modern era is undergoing a new revolution with the advent of Artificial Intelligence (AI). AI is a field of computer science which deals with the development of programs or computational models that are inspired by the human brain’s ability to learn and adapt.1 Perhaps the most prominent advancement AI contributes is generative AI, which has led to the development of robotic “human-like” tools that can generate text, audio, images, and even video with a simple prompt. The widespread and mainstream use of some of these tools, namely ChatGPT, Google Gemini, and Perplexity AI, has revolutionised almost all walks of life, from industry to academia.2 The scope of this article will be limited to the implications of generative AI in academic research writing, particularly in the field of medicine.